Assessment of heavy metals associated health risk to humans from biota in Thane creek, India - Sugandhi Suresh; Harshali S. Suryavanshi; Mahesh Tiwari; Vandana A. Pulhani (Discover Environment)
Abstract Industrialisation and urbanisation have led to significant contamination of the coastal environment with heavy metals. The objective of this study was to investigate the levels of V, Cr, Mn, Fe, Ni, Cu, Zn, and Pb in crab, prawn, and fish collected from Thane creek, Mumbai and determine the health risks posed to humans. The concentration of heavy metal in the edible parts of the biota was analysed using Energy Dispersive X-ray Florescence. The order of the concentration of the heavy metals in the studied biota species was crab > prawn > fish and this may be due to the habitat of crab, environmental factors, controlling mechanisms etc. The concentration of Fe was highest and Pb was lowest in crab, prawn and fish. The health risks to humans were estimated via estimated daily intake, hazard quotient and hazard index. It was observed that the estimated daily intake of biota was below the permissible exposure limit of daily dietary intake of each metal. The hazard quotient and hazard index of the analysed biota was less than unity, indicating no serious potential health risk to humans.